Association of gender and length of stay among Puerto Ricans hospitalized with decompensated heart failure. Issue 29 (July 2016) - Alnajashi, Mohammad A.; Almasoud, Mohammed A.; Aldaham, Sami A.; Acuña, Juan Manuel; Zevallos, Juan C.
Abstract : Abstract: Heart failure (HF) is a serious, chronic, and progressive condition which may require hospitalization if decompensated. Each year, in the UnitedStates, there are approximately 1 million hospitalizations due to decompensated HF at a cost of 39 billion. Because limited information examining the association between gender and length of stay (LOS) is available in the published literature for Puerto Ricans hospitalized with decompensated HF, we aim to investigate gender differences related to LOS in this population. This study is a secondary data analysis of the Puerto Rico Cardiovascular Disease Surveillance System database, which is a nonconcurrent prospective study carried out in 2007 and 2009. LOS was dichotomized into ≤5 days or ≥6 days (extended) categories. The χ 2 test was used to examine associations between categorical variables. Binary logistic regression was used to estimate unadjusted and adjusted odds ratios of extended LOS. Collinearity was assessed using Pearson correlation coefficients. A P value of 0.05 and 95% confidence intervals were used to evaluate statistical significance. A total of 1724 patients (47.6% women) comprised our study population. The average age of women was 72.5 ± 13.4 years; the average age of men was 67.2 ± 14.5 years. For both women and men, median LOS was 5 days (interquartile range = 5 days). Women were more likely than men to have diabetes mellitus, hypertension, and dyslipidemia, but current smoking was higher in men than in women. The proportion of patients with extended LOS was similar for men (43.3%) and women (45.1%) ( P = 0.448). Likewise, the odds for extended LOS was comparable for both genders (OR = 1.1, 95% CI = 0.9, 1.4). Patients admitted with recurrent decompensated HF hospitalizations had shorter LOS than patients with initial episodes (OR = 0.7, 95% CI = 0.6, 0.9). However, factors that prolonged the LOS included the presence of renal failure (OR = 1.7; 95% IC = 1.3, 2.1) and ejection fraction (EF) <35% (OR 0.7; 95% CI 0.6, 0.9). Although we were not able to find statistically significant association between LOS and gender in Puerto Rican patients hospitalized with decompensated HF our findings suggest that incidental episodes and having an EF <35% increase the odds of extended LOS.